PARTISIPASI PEMUDA DALAM PENGEMBANGAN KAWASAN EKOWISATA DAN IMPLIKASINYA TERHADAP KETAHANAN MASYARAKAT DESA (Studi di Kawasan Ekowisata Gunung Api Purba Nglanggeran, Desa Nglanggeran, Kecamatan Patuk, Kabupaten Gunung Kidul, DIY - Rosida, Idah (Jurnal Ketahanan Nasional, 2014)
The youth in Nglanggeran Village actively participated in developing the village potential namely established Nglanggeran Ancient Volcano as ecotourism area. The youthâs participation was embodied in thought, energy, materials, skill and intelligence, and social participation to supported the Nglanggeran Ancient Volcano ecotourism area development. This purposeâs research was to found out how the youth participate in developing Nglanggeran ecotourism area and its implication on village communityâs resilience. The research was conducted with hinterview method and field observation with purposive sampling and analyzed with qualitative descriptive method. The implication of ecotourism area development on village community was over the economic, social community, environment preservation, infrastructure establishment, and youth establishmentâs resilience at Nglanggeran Village. Therefore the youthâs participation involvement had to be enhanced to hastened the villageâs area development.Keywords: Participation, Ecotourism Area, Villageâs Community Resilience